The “Ambiguous Sex”: Cross-dressing heroines in Sensation and New Woman fiction - Katherine MANSFIELD (E-REA)
As exemplified by Louisa May Alcott’s “Behind a Mask” (1866), Sensation fiction is a genre preoccupied with questioning notions of Victorian femininity. However, while heroines like Jean Muir have the power to use their feminine identity to suit their own intentions, other Sensation novels, including Albert Eubule Evans’ Revealed at Last (1873), challenge assumptions regarding the inherent binary of gender through their use of cross-dressing heroines. Anticipated by Evans’ portrayal of his cross-dressing heroine, New Woman novels such as Lady Florence Dixie’s Gloriana; or, the Revolution of 1900 (1890) and George Moore’s “Albert Nobbs” (1927) also contested the contemporary conviction that gender was inseparable from anatomical sex, and that masculinity and femininity were two distinct categories. However, unlike Evans’ novel where the ability to alter one’s gender is based on a performance of masculinity, Dixie and Moore suggest that masculinity is biologically inherent in women. By focusing on the figure of the cross-dresser in Florence Marryat’s Her Father’s Name (1876) and Sarah Grand’s The Heavenly Twins (1893), this essay challenges twentieth-century mis-readings of nineteenth-century gender theory, specifically the two-sex model Thomas Laqueur in Making Sex: Body and Gender from the Greeks to Freud (1990) identifies as holding precedence in the Victorian period. This essay argues that Laqueur disregards the forward-thinking narratives of Sensation and New Woman fiction in which ideas about women and gender are radically challenged.